2009
DOI: 10.2131/jts.34.295
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of tellurium, antimony and germanium simultaneously administered to rats

Abstract: -Recently, tellurium (Te), antimony (Sb) and germanium (Ge) have been used as an alloy in phase-change optical magnetic disks, such as digital versatile disk-random access memory (DVD-RAM) and DVD-recordable disk (DVD-RW). Although these metalloids, the so-called "exotic" elements, are known to be non-essential and harmful, little is known about their toxic effects and metabolism. Metalloid compounds, tellurite, antimonite and germanium dioxide, were simultaneously administered to rats. red blood cells (RBCs):… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…22,51 The accumulation in RBCs was also observed when Te or arsenic was ingested. As mentioned above, the accumulated species of Te and arsenic were the dimethylated forms.…”
Section: ·2 Metabolism Of Antimony Based On the Characterizationmentioning
confidence: 97%
See 2 more Smart Citations
“…22,51 The accumulation in RBCs was also observed when Te or arsenic was ingested. As mentioned above, the accumulated species of Te and arsenic were the dimethylated forms.…”
Section: ·2 Metabolism Of Antimony Based On the Characterizationmentioning
confidence: 97%
“…21 The gel filtration column is able to separate antimony(V) citrate from free Sb(V) ions in urine. 22 Other chromatographic mechanisms, such as multi-mode gel filtration and cation-exchange chromatography, are also effective to separate organic Te metabolites. 23 As mentioned above, the advantage of utilizing a gel filtration column is that the separation conditions are similar to the physiological conditions.…”
Section: ·2 Speciation and Hyphenated Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal experimental results showed that germanium compounds, both inorganic and organic, are rapidly and almost completely absorbed into the lungs and gastrointestinal tract mucosa [2] [4]. The germanium and plasma proteins can be transported in an unbound state if they are injected into the blood directly, and are excreted by both the kidney and the gastrointestinal tract, where the kidney is the chief excretory organ (80% versus 13%) [5] [6] [7]. Chart 1.…”
Section: Absorption and Metabolismmentioning
confidence: 99%
“…Germanium enters the organism and binds to hemoglobin, thereby ensuring normal cellular aerobic metabolism [46]. In addition, the germanium compounds can capture the hydrogen ions and other harmful ions in the metabolites, and play a role in purifying blood at different degrees [47].…”
Section: Participation In the Metabolism Of Oxygen In Vivomentioning
confidence: 99%